Analisis Yuridis Pembentukan Koperasi Desa dan Kelurahan Merah Putih sebagai Instrumen Pemberdayaan Ekonomi Masyarakat - Efrilia Yusri; Muhammad Islahuddin (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2026)
The Merah Putih Village and Sub-district Cooperative (KDKMP) is a government policy directed at strengthening the community economy through cooperative institutions based on the principles of family values, mutual cooperation, and economic self-reliance. The establishment of KDKMP is part of efforts to empower the economy of village and sub-district communities, yet its implementation requires an assessment of the suitability of its legal basis, formation mechanism, and legal standing within the Indonesian legal system. This study aims to analyze the juridical basis for the establishment of KDKMP and examine its position as an instrument of community economic empowerment. The method used is normative legal research with a statute approach and a conceptual approach, employing primary, secondary, and tertiary legal materials analyzed qualitatively and systematically. Research findings indicate that the establishment of KDKMP is grounded in Article 33, Paragraph (1) of the 1945 Constitution, Law Number 25 of 1992 concerning Cooperatives, and Presidential Instruction Number 9 of 2025. KDKMP serves as an instrument for community economic empowerment by expanding economic access, enhancing business self-reliance, and strengthening local economic potential. The study also identifies a need to strengthen regulations and institutional frameworks to ensure legal certainty and support the optimal implementation of KDKMP.